From Classical Compositions to Contemporary Seriality. (2nd April 2021) - Janhsen, Angeli
Abstract : Classical compositions, such as those of Claude Lorrain (1600–1680), show balanced situations where the depicted objects seem to represent beauty – they appear to exist in an ideal order; they seem right, once and for all. They allow their viewers, who live in a contingent world, believe that unity and beauty are attainable. English landscape gardens in the eighteenth century offered viewers the experience of moving in real settings that seem to reproduce the canvasses of classical landscape painting. Contemporary visitors know this is an imitation; they appreciate that this is not everyday reality but a kind of realized utopia. Artworks such as the early ones by Rembrandt Harmenszoon van Rijn (1606–1669) and those from the nineteenth century onwards (Paul Cézanne, Claude Monet), make us understand that a final rightness is not possible; that it is only possible to try again and again to attain the real – without ever arriving at the one right solution. In their endeavour to depict reality, these artists engage in a serial elaboration of the same subjects and objects of their art. These series of nearly the same subjects invoke the impossibility of getting it right once and for all. Piet Mondrian illustrates the development from seriality, as repeated attempts to depict the same with a difference, to the practice of seriality as an experiment in symmetry and balance that both goes back to Claude Lorrain and modernizes the concept of the ideal for application to abstract art. In contemporary art after the Second World War serial structures in single artworks were common, thus superseding compositions with their discredited promise of ideality. Series occurred not only in the contemporary visual arts, but also in literature, music and in the theatre. The repetitive structures of Minimal Art offer to the beholder the possibility of experiencing 'reality' in an age of media and fakes. My example will be the repetitive structures of Christian Boltanskiʼs oeuvre which provides an opportunity to reflect on the similarity and difference of people in contemporary democracies. My main argument is therefore that the change from composition to seriality corresponds to historical change.